Comprehensive analysis of transcriptome and metabolome identified the key gene networks regulating fruit length in melon - Qingtao Wang; Lingli Tang; Yuhua He; Yongyang Xu; Jian Zhang; Weihu Kong; Keyun Hu; Jordi Garcia-Mas; Marta Pujol; Guangwei Zhao (BMC Plant Biology)
Abstract Background Melon is an ideal crop model for studying fruit development. Fruit shape is an important quality trait, and fruit length is a key indicator affecting fruit shape. However, studies on the genes regulating melon fruit length are still limited. Results In this study, we investigated the gene network regulating fruit morphology in melons utilizing transcriptome profile and a co-expression pattern-based approach. Four co-expression modules/gene networks highly correlated with changes in endogenous plant hormone levels at different developmental stages were identified. We pinpointed 11 key genes associated with cell development, 4 genes related to microtubule development, and 16 genes involved in the auxin (IAA, indole-3-acetic acid) pathway. These genes were identified as module hubs, and their expression level correlated with phenotypic variation. Through rigorous screening methods, we enhanced the likelihood that these genes are genuine candidates in the regulation of the fruit morphology network. These genes play a significant role in controlling fruit length, providing crucial insights into the molecular mechanisms underlying melon fruit development. Conclusions Our findings revealed candidate genes that regulate melon fruit length, helping in the understanding of the molecular mechanisms underlying melon fruit development. These genes will be valuable for implementing marker-assisted breeding strategies.